NomaTrack and the LoRa-DTN protocol : DTN in innovation for reindeer husbandry - Udén, Maria; Grasic, Samo; Kerstin Kemlén, Kerstin; Annelie Päiviö, Annelie (Luleå tekniska universitet, Människa och teknik, 2021)
The NomaTrack design combines the LoRa‐DTN protocol with a set of unique equipment units. The equipment set consists of the units base station, reindeer GPS collar, and portable node. Drones are utilized to create line‐of‐sight. With this set reindeer positions are tracked. Real life on‐site tests integrated in herding operations were essential. They involved Jåhkågaska, Sirges, Tuorpon and Udtja Sámi Villages in Norrbotten, Sweden. In the concluding tests November‐December 2020 the deployed network extended reindeer tracking beyond regular infrastructure and connectivity with approximately 300 units. The system remains in use after the project ended. From mid‐November totally 5000 or up to more than 6000 bundles were delivered daily. Into January the number of active nodes in the LoRA‐DTN has been about 145 to 180 per day. The NomaTrack connectivity concept offers an opportunity for messaging. During the project here reported, the design of such a service was drafted. Development ofthe messaging function will commence during 2021. Sponsorship of NomaTrack and the LoRaDTN protocol 2020. Project support from Google Planeringsverktyg för rennäringsföretag - teknikutveckling inom renskötseln, Europeiska Jordbruksfonden för Landsbygdsutveckling